Creative Work Conditions, Contexts and Practices - Andersson Cederholm, Erika; Lindqvist, Katja; de Wit Sandström, Ida; Warkander, Philip (Routledge Research in the Creative and Cultural Industries, 2024)
How do creative workers work? This book brings together insights from a range of relevant disciplines to help answer this significant research question. Featuring case studies from the European context, contributors tap into the experiences and practices from creative workers, demonstrating their attempts to navigate a changing environment which affects spaces, identities, and professional roles. As cross-disciplinary re-thinking of work, labour processes and management practices in the creative and cultural industries, the book offers perspectives on the importance of highlighting creative work as a phenomenon and practice beyond a particular industry, market, or public sector. Providing an opportunity to expand our conception of what creative work is, the book draws on studies of a range of activities, practices and sectors that are usually included in the cultural and creative industries as well as ones that are more untraditional. The result is a volume that will interest students, practictioners, and scholars with an interest in the creative industries. The Open Access version of this book, available at www.taylorfrancis.com, has been made available under a Creative Commons Attribution-Non Commercial-No Derivatives (CC-BY-NC-ND) 4.0 license.